College Students' Perceptions of Body Shaming: A Study of the Influence of Social Norms on Individual Views - Ainul Mardiyah; Hainun Hanifah; Muhammad Farid Akbar (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
This study aims to examine in depth students' perceptions of body shaming, reveal the influence of social norms and media representations in shaping students' experiences and responses to this phenomenon, and identify the coping strategies they adopt. Using a qualitative approach with in-depth interviews of students from various departments at the University of North Sumatra (USU), this study analyzes the collected data to identify key themes and build a comprehensive understanding of the issue of body shaming in the campus environment. The results of the study show a significant prevalence of body shaming, which has a negative impact on students' mental health. Social norms that glorify narrow beauty standards, reinforced by dominant media representations, contribute to the formation of negative perceptions of the body and experiences of body shaming. Students develop various coping strategies, but integrated intervention efforts are needed to create a more inclusive and supportive campus environment.